Clinico-etiological profile and antimicrobial susceptibility pattern of bacterial keratitis in the era of automated platforms - Dr. Ranjana Rohilla; Dr. Aroop Mohanty; Dr. Suneeta Meena; Dr. Neelam Kaistha; Dr. Pratima Gupta (Tropical Journal of Pathology and Microbiology, 2021)
Background: Microbial keratitis is one of the most significant causes of blindness in our country. Knowledge regarding the aetiology and antibiotic sensitivity pattern in a specific region is crucial for the ideal management of these infections.Materials and Methods: A prospective study where corneal scrapings from 161 suspected cases of microbial keratitis were collected and were subjected to direct microscopy by gram stain and bacterial culture and identification as well as antibiotic sensitivity testing.Results: A total of 57 samples turned out to be positive out of the total 161 and were shared equally by both gram-positive and gram-negative bacteria. All these culture-positive bacteria were also identified by MALDI TOF-MS and were speciated. Few rare organisms which could not be identified by conventional means were also recovered using the same. Most of the gram-positive isolates showed good sensitivity to vancomycin and ciprofloxacin whereas Pseudomonas spp was found to be resistant to the aminoglycosides.Conclusion: Right knowledge about the local profile of bacterial causes of keratitis along with its antibiotic resistance pattern will help the clinicians immensely and help them to initiate the correct empirical therapy bases on the smear results without wasting crucial time.